(untitled) (Journal of Solar Energy Research Updates, 2019)
This paper presents a practical design of combination solar photovoltaic panel (PV) and an ordinary flat-plate air heating solar collector (FPSC. (The offered collector generated both electrical and thermal power for many applications such as (drying, heating, cooling, etc...). The PV cells are placed in the entrance of the (FPSC), the design avoids the temperature increasing of the PV. In this paper the photovoltaic thermal (PV/T) collector energy analysis were carried out. A mathematical model has been built in order to determine the optimum contribution ratio of the PV cells in the offered collector. The model takes into account the variation of the electrical characteristics with solar radiation and the PV cell’s temperature. The obtained results have shown that for a (PV/T) collector of 3m long, the maximum energy extracted from the collector, when the length of the PV panel is 2.4 m and the rest of the collector is ordinary FPSC. Furthermore, the electrical efficiency and the thermal efficiency of the PV/T system was found to be higher than that of the conventional separated systems.